Orkes Keroncong Nada Kasih di Yogyakarta dan Peranannya dalam Melestarikan Nasionalisme Musik Keroncong - Wisnu Mintargo; Iwan Budi Santoso; Andre Indrawan (Promusika: Jurnal Pengkajian, Penyajian, dan Penciptaan Musik, 2019)
This study examines the activities of the Orkes Keroncong (OK) Nada Kasih conducted by Fx Supardi who has given a positive impact on the development of Keroncong music in the Sleman Regency of Yogyakarta. This research reveals how the efforts made by Fx Supardi with his OK Nada Kasih in conserving the keroncong music. To answer these problems, this study utilizes descriptive qualitative methods. This study concludes that the OK Nada Kasih’s programs aim to conserve and develop keroncong music so that it will be favored by the Indonesian community, especially the younger generation. Its program that encompasses public performances, social gatherings, and other social activities has made this band continues to work as the potential keroncong orchestra. By consistently developing as well as disseminating its keroncong music repertoire this band has given a great contribution to public services in strengthening national identity so that public services in developing the nation have chronologically improved.